Study of the Application of Gamification in Korean Language Learning Applications - Revi Ananda Kirana Putri; Anita Fira Waluyo (Jurnal Informasi dan Teknologi, 2024)
This study aims to analyze the application of gamification in a mobile-based Korean language learning application. The increasing popularity of mobile devices and the demand for interactive learning experiences make mobile apps a commonly used tool in language learning. Gamification, applying game design elements in a non-game context, has increased user motivation and engagement. This study investigates how gamification elements such as points, badges and leaderboards can be integrated into a mobile language learning app aimed at Korean language beginners to enhance the learning experience. Qualitative research methods were used, involving developing and implementing a prototype app integrating gamification elements. The research participants were beginners who had just started learning Korean and were asked to use the app for a period of time. During post-use interviews, data was collected to evaluate the effectiveness of gamification in increasing engagement and motivation. The results showed that gamification elements significantly increased user engagement and motivation, improving learning outcomes. The addition of features such as progression levels and daily challenges was also shown to encourage users to be more consistent in learning. The spiral development method was applied to this application. This method involves iterative iterations between planning, development, testing and evaluation, allowing for improvements based on user feedback. Each development cycle focused on refining the gamification elements and improving the app's functionality.